Proceedings of the 60th Annual Meeting of the Association for Computational Linguistics (Volume 1: Long Papers) 2022
DOI: 10.18653/v1/2022.acl-long.318
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Moments of Change from Longitudinal User Text

Abstract: Identifying changes in individuals' behaviour and mood, as observed via content shared on online platforms, is increasingly gaining importance. Most research to-date on this topic focuses on either: (a) identifying individuals at risk or with a certain mental health condition given a batch of posts or (b) providing equivalent labels at the post level. A disadvantage of such work is the lack of a strong temporal component and the inability to make longitudinal assessments following an individual's trajectory an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 29 publications
0
23
0
Order By: Relevance
“…As per (Tsakalidis et al, 2022b), the evaluation is carried out using two types of metrics. The first one is post-level metrics, which assesses the model's performance using precision, recall, and F1 score.…”
Section: Evaluation Metricsmentioning
confidence: 99%
See 1 more Smart Citation
“…As per (Tsakalidis et al, 2022b), the evaluation is carried out using two types of metrics. The first one is post-level metrics, which assesses the model's performance using precision, recall, and F1 score.…”
Section: Evaluation Metricsmentioning
confidence: 99%
“…In this paper, we explain our approach to the CLPsych (Tsakalidis et al, 2022a) shared task, which consists of two subtasks, as follows: Subtask A: Subtask A tries to capture those moments when a user's mood deviates from their baseline mood based on a user's postings throughout a specific time period -this is a post-level sequential classification task. The full task description can be found in (Tsakalidis et al, 2022b). Subtask B: A user-level classification task on predicting the degree of suicide risk.…”
Section: Introductionmentioning
confidence: 99%
“…They found that adding the year as a prefix to the input aided learning of seen facts, improving performance on predictions of future events. Tsakalidis et al (2022b) identify individuals' changes in mental health over time. This temporal dimension can be helpful in monitoring clinical outcomes and it can also help online platform moderators prioritize interventions depending on an individual's vulnerability at a certain moment in time.…”
Section: Related Workmentioning
confidence: 99%
“…We incorporate such information both through sequence models such as LSTMs (Hochreiter and Schmidhuber, 1997) that encode and preserve information from previous data points to make predictions, as well as through explicit custom features representing the time between data points, which we refer to as time lag features. We choose RoBERTa as a base for our models, as (Tsakalidis et al, 2022b) find BERT-based models perform well on this task, and RoBERTa models frequently outperform BERT in practice (Liu et al, 2019).…”
Section: Approachmentioning
confidence: 99%
See 1 more Smart Citation